Winning Guinea-Bissau for Jesus: The Guinean Evangelical Minority, from the Origins to the Present. (22nd March 2018) - Formenti, Ambra
Abstract : This article analyses the historical course of the Evangelical minority in Guinea-Bissau, its transformations, its recent expansion and its current engagement with the public sphere. First, I trace the trajectory of the Guinean Evangelical movement from the 1940s to the present, against the background of the process of decolonization and the post-Independence history of the country. Second, I examine the recent impact of Pentecostal and Charismatic forms of Christianity on local Evangelical churches, following the transnational circulation of believers and missionaries, on the one hand, and the arrival of new international churches, mostly from Brazil and other African countries, on the other. Third, I place the current flowering of Evangelical and Pentecostal denominations in the broader context of a general shift to universal religions throughout the country. Within this framework, I argue, this success can be read as expression of a widespread craving for modernity and mobility, both in rural and urban Guinea-Bissau.